(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the functional & radiological outcome in nonunion of scaphoid fractures – fixed with Matti-Russe grafts. Study Design: Prospective Interventional Case Series. Place and Duration of Study: This study was conducted at the Ameer-ud-Din Medical College, Lahore/ General Hospital, Lahore from June 2015 to June 2018. Materials and Methods: A total of 20 patients included having age between 18-50 years with more than 4 months old fractures in scaphoid. All the fractures were treated before conservatively. The follow up was carried out at 3 and 6 months post-operatively. Both radiological evidences and functional assessment carried out and documented in Mayo’s wrist score. Results: The mean age was 31±8 years with male preponderance. Most of the patients have mean duration of injury 6±2 months. Almost half of the patients were having avascular necrosis (AVN) of the proximal pole of scaphoid. 75% of the patients resulted in good radiological healing and Mayo’s Wrist Score (MWS) have value as pre op MWS 53 to post op MWS 84 which is statistically significant. Conclusion: The results of both functional & Radiological data showed promising outcome with this technique so we conclude that Matti-Russe procedure is very effective procedure for nonunion of scaphoid but we recommend comparative study of different treatment options.